2017
DOI: 10.1098/rspb.2016.2675
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell structure in Caiman latirostris eggs improves embryo survival during nest inundation

Abstract: Egg inundation often results in poor hatching success in crocodylians. However, how tolerant eggs are to submergence, and/or how eggshell ultrastructure may affect embryo survival when inundated, are not well understood. In this study, our objective was to determine if embryo survival in Caiman latirostris is affected by eggshell surface roughness, when eggs are submerged under water. Tolerance to inundation was tested early (day 30) versus late (day 60) in development, using eight clutches (four per time trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Schleich & Kästle ; Cedillo‐Leal et al . ). The crystals forming crocodylian eggshell are usually wedge shaped (Mikhailov ; Choi et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Schleich & Kästle ; Cedillo‐Leal et al . ). The crystals forming crocodylian eggshell are usually wedge shaped (Mikhailov ; Choi et al .…”
Section: Resultsmentioning
confidence: 97%
“…Experimental approaches to test its possible role(s), such as those implemented by Cedillo‐Leal et al . () for crocodylian eggshells, as well as detailed observations on the nesting microenvironments of megapodes and Gekko gecko , compared with those of other avian and gekkotan taxa, could help to clarify the evolutionary significance of eggshell ornamentation. This in turn might offer further insights into the reproductive palaeobiology of other dinosaurian and squamate clades with ornamented eggshells (Mikhailov ; Fernandez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Through the magnifying glass and SEM, we were able to distinguish structures already reported in previous studies for C. latirostris, such as the calcite layer crossed by pores and remains of protein membrane 3,6,7 . We also observed that eggshells had an ornamentation, made up of columnar structures, some of them joined by bridges (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, there is evidence that the morphology of the eggshell changes during incubation. The outer surfaces of crocodilian eggshells develop erosion craters as incubation progresses in association with an acidic environment created by rotting vegetation that forms the nest mound (Cedillo-Leal et al, 2017;Ferguson, 1981Ferguson, , 1985Schleich & Kästle, 1988). Avian eggs lose calcium carbonate due to embryonic dissolution of the inner part of the eggshell (Simkiss, 1980), which can even lead to changes in eggshell gas conductance as seen in megapode eggs (Booth & Thompson, 1991).…”
Section: What Is the Role Of The Testudine Eggshell?mentioning
confidence: 99%
“…If the postulated hypothesis that shell thickness reflects the nesting environment has any validity then it should also apply to other reptilian taxa. Crocodilian eggshells are also thick for their egg mass (Figure 3) and the outer surface is regularly etched by the acidic conditions created by the decomposing nest materials (Cedillo-Leal et al, 2017;Ferguson, 1981Ferguson, , 1985Schleich & Kästle, 1988). Unincubated eggs or those incubated artificially outside of vegetation do not exhibit this erosion of the outer shell surface (Marzola, Russo, & Mateus, 2015).…”
Section: Variation In Eggshell Thickness and Physical Defence For Burmentioning
confidence: 99%